New developments in the biology of fibroblast growth factors. Issue 4 (9th February 2022) - Ornitz, David M.; Itoh, Nobuyuki
Abstract: The fibroblast growth factor (FGF) family is composed of 18 secreted signaling proteins consisting of canonical FGFs and endocrine FGFs that activate four receptor tyrosine kinases (FGFRs 1–4) and four intracellular proteins (intracellular FGFs or iFGFs) that primarily function to regulate the activity of voltage‐gated sodium channels and other molecules. The canonical FGFs, endocrine FGFs, and iFGFs have been reviewed extensively by us and others. In this review, we briefly summarize past reviews and then focus on new developments in the FGF field since our last review in 2015. Some of the highlights in the past 6 years include the use of optogenetic tools, viral vectors, and inducible transgenes to experimentally modulate FGF signaling, the clinical use of small molecule FGFR inhibitors, an expanded understanding of endocrine FGF signaling, functions for FGF signaling in stem cell pluripotency and differentiation, roles for FGF signaling in tissue homeostasis and regeneration, a continuing elaboration of mechanisms of FGF signaling in development, and an expanding appreciation of roles for FGF signaling in neuropsychiatric diseases. This article is categorized under: Cardiovascular Diseases > Molecular and Cellular Physiology Neurological Diseases > Molecular and Cellular Physiology Congenital Diseases > Stem Cells and Development Cancer > Stem Cells and Development Abstract : Regulation and functions of the FGF signaling pathway.